Surgical treatment of gingival pigmentation versus laser: Efficacy, aesthetic and functional outcomes (Research, Society and Development, 2024)
This study aimed to investigate the approaches and outcomes of surgical treatment of gingival pigmentation compared to laser treatment, aiming to understand the efficacy and aesthetic and functional outcomes associated with these procedures. It is an integrative review that included studies with primary data published between January 2015 and November 2023, in English, Portuguese and Spanish languages, excluding case reports, abstracts and editorials. The descriptors/keywords used were: "Aesthetic and Functional Outcomes"; "Gingival Dyschromia"; "Gingival Pigmentation"; "Laser Treatment"; "Surgical Interventions". The databases ScienceDirect, PubMed and SciELO were selected. After applying the eligibility criteria, 113 studies were identified in the databases, and 6 were selected to compose the final sample of this review. The selected studies aimed to evaluate gingival depigmentation techniques, such as surgery with scalpel, injection of vitamin C, and application of Nd: YAG, diode and Er,Cr: YSGG lasers. By investigating the approaches and outcomes of surgical treatment of gingival pigmentation compared to laser treatment, it was found that the results obtained from the various studies analyzed provide a comprehensive overview of the current scenario of these interventions, providing important information for clinical practice, such as versatility in treatment, patient comfort and effectiveness in healing.